Influence of muscle regions of meridians needling method combined with auricular point sticking on pain and range of motion in patients with chronic nonspecific low back pain - Shan, Yunping; Ma, Yinhua; Su, Baoqing (Journal of acupuncture and tuina science, 2024)
Objective To observe the effects of muscle regions of meridians needling method combined with auricular point sticking on pain and lumbar range of motion in patients with chronic nonspecific low back pain. Methods A total of 100 patients with chronic nonspecific low back pain were randomly divided into a control group and an observation group, with 50 patients in each group. Both groups received auricular point sticking treatment, while the control group received additional conventional acupuncture treatment, and the observation group received additional muscle regions of meridians needling method. The total effective rate of the two groups was compared after 4 weeks of treatment. Before treatment and after 1 week and 4 weeks of treatment, the visual analog scale (VAS) score was used to assess the degree of low back pain, and the modified-modified Schober (MMS) score was used to evaluate the lumbar range of motion. Results There was statistical significance in comparing the total effective rate between the two groups ( P <0.01). During the treatment process, as the number of treatments increased, the VAS score gradually decreased, and the MMS score gradually increased in both groups. After 1 week and 4 weeks of treatment, the VAS score in the observation group was lower than that in the control group ( P <0.01), and the MMS score in the observation group was higher than that in the control group ( P <0.01). During the treatment period, no serious adverse reactions occurred in either group. Conclusion Based on auricular point sticking treatment, muscle regions of meridians needling method is more effective than conventional acupuncture in treating chronic nonspecific low back pain since it is able to significantly reduce the pain and improve the lumbar range of motion.